(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Adult onset still Disease is a multi-systemic auto inflammatory disorder manifesting as high fever spikes, evanescent rash and polyarthralgias. It has a bimodal age distribution with peak incidence in adults aged 15 to 25 and 36 to 45 years. Here we describe a case of a 35 year old male who presented in a tertiary care hospital with the complaints of fever, rash and joint pains, and negative rheumatoid factor and raised ESR and CRP levels. After excluding infectious and other autoimmune disorders, he was diagnosed as a case of Adult Onset Still Disease using the Yamaguchi and Fautrel Criteria. He showed a favorable response to steroid therapy and disease remission was attained. The patient was then started on a maintenance therapy of methotrexate. This case demonstrated the diagnostic challenges of AOSD and the importance of considering it as a differential while pyrexia of unknown origin (PUO) is encountered. While early diagnosis and treatment has a good prognosis.